Associations between the use of aspirin or other antiplatelet drugs and all-cause mortality among patients with COVID-19: A meta-analysis - Su, Wanting; Miao, He; Guo, Zhaotian; Chen, Qianhui; Huang, Tao; Ding, Renyu (Frontiers in Pharmacology, 2022)
Abstract Introduction: Whether aspirin or other antiplatelet drugs can reduce mortality among patients with coronavirus disease (COVID-19) remains controversial. Methods: We identified randomized controlled trials, prospective cohort studies, and retrospective studies on associations between aspirin or other antiplatelet drug use and all-cause mortality among patients with COVID-19 in the PubMed database between March 2019 and September 2021. Newcastle–Ottawa Scale and Cochrane Risk of Bias Assessment Tool were used to assess the risk of bias. The I² statistic was used to assess inconsistency among trial results. The summary risk ratio (RR) and odds ratio (OR) were obtained through the meta-analysis. Results: The 34 included studies comprised three randomized controlled trials, 27 retrospective studies, and 4 prospective cohort studies. The retrospective and prospective cohort studies showed low-to-moderate risks of bias per the Newcastle–Ottawa Scale score, while the randomized controlled trials showed low-to-high risks of bias per the Cochrane Risk of Bias Assessment Tool. The randomized controlled trials showed no significant effect of aspirin use on all-cause mortality in patients with COVID-19 (risk ratio [RR], 0.96 [95% confidence interval [CI] 0.90–1.03]). In retrospective studies, aspirin reduced all-cause mortality in patients with COVID-19 by 20% (odds ratio [OR], 0.80 [95% CI 0.70–0.93]), while other antiplatelet drugs had no significant effects. In prospective cohort studies, aspirin decreased all-cause mortality in patients with COVID-19 by 15% (OR, 0.85 [95% CI 0.80–0.90]). Conclusion: The administration of aspirin may reduce all-cause mortality in patients with COVID-19.